(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
This study aimed to acknowledge the attitudes of teachers in the inclusion of people with disabilities in the ordinary classes the cities of Homs and Tartous. A questionnaire was distributed to measure the attitudes of teachers towards integrating students with disabilities with ordinary students. The questionnaire included three dimensions ( the social, the academic and the psychological). The study community consists of teachers who study in the first and second basic education cycle. The study found that there is a statistically significant difference between the average score of teachers towards integration on the trend scale according to the governorate variable in favor of Homs governorate, and the existence of statistically significant difference between the average males and females to merge the two dimensions Social and psychological benefit for males and there is ‘not difference between the average of males and females towards integration on the academic dimension. The study also found statistically significant differences between the average grade of teachers towards integration on the academic dimension due to the variable years of experience for teachers with more than ten years’ experience. In addition, there is a statistically significant difference between the average teachers’ Educational stage in favor of the first cycle of basic education.